'Tackling inequality': Australian Labor Party ideology and discourse under Bill Shorten. Issue 4 (2nd October 2022) - Falcinella, Nick
ABSTRACT: While it is often claimed that the Australian Labor Party was 'bolder' under Bill Shorten than under both Kevin Rudd and Julia Gillard, the party's discourse and ideology of this period has not yet been comprehensively examined. Framed in the 2019 election as 'shifty', Shorten is arguably best remembered for his lack of popularity; yet this obscures the degree of ideological transformation he oversaw. In this article, I analyse key speeches and policy documents to transcend superficial impressions and examine Shorten Labor's revised discursive framings and ideological positions. While not without ideological contradiction, notably regarding Labor's own neoliberal economic reform legacy, I find Shorten's leadership represented a significant progressive reorientation of ALP ideology and discourse on both economic and social issues, particularly compared to Gillard. Specifically, Shorten Labor articulated a socially progressive and inclusive social democratic politics that was once-again prepared to critique markets and their role in producing inequality.